Determinants of voter turnout in Nsukka Council of Enugu State, South Eastern Nigeria - Nwankwo Cletus Famous (Bulletin of Geography. Socio-Economic Series, 2019)
Voting is becoming of significance in Nigeria, as in many other countries in Africa. Although Nigerian electoral politics has attracted full attention from scholars, there is little research on the factors that determine voter turnout in the country at the local level, especially the South-East geopolitical zone (GPZ). This paper is a stepwise logistic regression analysis of the determinants of voting in Nsukka council in Enugu State, South-East GPZ of Nigeria. The results show that age (0.230), education (0.532), marital status (1.355), political trust (1.309) and partisanship (˗0.570) are significant predictors of voter turnout. The effect of age, education, marital status and political trust on voting is positive and statistically significant, but partisanship has a statistically significant negative relationship with voting (p<0.01). The paper highlights the importance of local level geographical differentials in the factors influencing voting in Nigeria.